Isolation and sensitivity patterns of Pseudomonas aeruginosa from nonclinical samples (African Journal of Biomedical Research, 2024)
The presence of pathogenic microorganisms in hospital environment  possesses obvious clinical risk to patients with some obvious consequences. The current study was conducted to ascertain the prevalence of Pseudomonas aeruginosa in nonclinical samples in central Hospital, Agbor. A total of 25 Pseudomonas aeruginosa were isolated from a total of 110 nonclinical samples collected intermittently from Sinks traps, Mop heads, bed pans from four (4). The samples were inoculated on MacConkey and blood agar plates and incubated at 37 °C for 24 h. The isolates were identified by conventional microbiological tests. Antimicrobial susceptibility pattern was determined by modified Kirby-Bauer disk diffusion method. The  overall prevalence  of  Pseudomonas aeruginosa  was 23.8% with a range of 16.2% to 33.2% in the wards examined. The most contaminated area with Pseudomonas aeruginosa was  sink traps (36.)%), floors (24.0%), mopheads (20.0%) while bedpans accounted for  20.0% of the isolate sources. the antibacterial susceptibility patterns of the Pseudomonas aeruginosa  to ten (10) antibacterial agents used showed  84% susceptibility to pefloxacin, 76% to ofloxacin, while ceftriaxone and ciprofloxacin recorded 72% susceptibility respectively. 64% of the isolates were susceptible to gentamicin. The  continued contamination of hospital  wards with   Pseudomonas aeruginosa highlights the necessity for robust infection control measures, ongoing monitoring and management of the hospital environment to minimize the risk of healthcare-associated infections
Keywords: Nosocomial Infection; Pseudomonas aeruginosa; antibacterial agents; cross infection; antimicrobial resistance